2011
DOI: 10.1371/journal.pone.0017175
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Cycle Analysis of Fission Yeast Cells by Flow Cytometry

Abstract: The cell cycle of the fission yeast, Schizosaccharomyces pombe, does not easily lend itself to analysis by flow cytometry, mainly because cells in G1 and G2 phase contain the same amount of DNA. This occurs because fission yeast cells under standard growth conditions do not complete cytokinesis until after G1 phase. We have devised a flow cytometric method exploiting the fact that cells in G1 phase contain two nuclei, whereas cells in G2 are mononuclear. Measurements of the width as well as the total area of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 11 publications
2
46
0
3
Order By: Relevance
“…Spd1 and Spd2 levels were monitored by western blotting. The fraction of S phase cells (Knutsen et al, 2011) peaked at 50% between 80 and 120 minutes. Unlike Spd1, Spd2 was not strongly downregulated at S phase.…”
Section: Cdt2mentioning
confidence: 99%
See 3 more Smart Citations
“…Spd1 and Spd2 levels were monitored by western blotting. The fraction of S phase cells (Knutsen et al, 2011) peaked at 50% between 80 and 120 minutes. Unlike Spd1, Spd2 was not strongly downregulated at S phase.…”
Section: Cdt2mentioning
confidence: 99%
“…interpretation of FACS data in fission yeast is complicated by the fact that G1 and S phase cells are still attached to their sisters, thus giving rise to a 2C signal. However, by measuring the DNA signal width, it is possible to discriminate G1 and S cells from G2 cells (Knutsen et al, 2011), thus giving a more precise estimate of the S phase population. By using this method, we found that overexpression of Spd2 caused a strong increase in the number of cells undergoing S phase, suggesting that the protein -similarly to Spd1 -delays DNA replication ( Fig.…”
Section: Spd1 and Spd2 Both Inhibit S Phasementioning
confidence: 99%
See 2 more Smart Citations
“…1D). It has been elegantly shown that other DNA-derived pulse parameters such as width can be utilised to distinguish G1 and G2 cells based on the assumption that cells with 2Â 1C nuclei should orientate through the long axis and as such have an increased time of flight through the laser beam that translates into an increased pulse width [4]. While this approach has merit, we feel that a truly accurate analysis of the fission yeast cell cycle requires an image-based approach due to the fact that not all cells will orientate correctly through the laser interrogation point and may rotate around the x, y and z axes (Fig.…”
Section: Introductionmentioning
confidence: 99%